Dipa Nusantara Aidit: Titik Balik PKI dalam Pemilu 1955 - Aldi Hendra Pratama; Rhoma Dwi Aria Yuliantri; Aman Aman (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
The resurgence of the Indonesian Communist Party (PKI) and its emergence as the fourth-largest party in the first general election of 1955 was founded upon a massive and strategic effort. This achievement is particularly notable considering the party’s failure in the 1948 Madiun rebellion, which severely tarnished its reputation and rendered its leaders fugitives. Although the party was not officially disbanded, rebuilding it from such a compromised position was a formidable challenge. This study employs a historical method to analyze the strategies utilized by Dipa Nusantara Aidit in revitalizing the PKI and enabling its active participation in Indonesian politics. The methodological stages include: (1) topic determination; (2) heuristics, involving the collection of relevant data and information; (3) source verification or criticism to assess the validity, authenticity, and credibility of the collected sources; (4) interpretation through analysis and synthesis of data; and (5) historiography, which entails the writing of a historical narrative based on the discovered facts. Under the revolutionary programs led by Dipa Nusantara Aidit as General Secretary, the PKI consolidated its foundation in the 1955 election by securing 39 seats in parliament and 80 seats in the Constituent Assembly. The strategies implemented encompassed party reorganization, the formation of a national front, empowerment of peasants, active support of the government, expansion of educational initiatives, and fostering close relations with President Soekarno and the Indonesian National Party (PNI).